Warthin’s tumor of Submandibular gland - Adhikari, P; Sinha, BK; Baskota, DK (Journal of Institute of Medicine Nepal, 2010)
Warthin's tumour is a benign tumour which is exceedingly rare in submandibular gland. Here, we report a case of warthin's tumour of submandibular gland in a 64 years old female which is treated with excision of tumour along with the gland. A brief review of literature is also included. Key words: Submandibular gland, warthin's tumour, cyst-adenolymphoma The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 42-43